Harmonisasi Produk Hukum Daerah dengan Prinsip-Prinsip Siyasah Dusturiyah dalam Pembentukan Peraturan Daerah di Indonesia - Akhmad Hafi; Noormala Santi; Akhmad Zaki i Yaman (PT. Pustaka Andil Lestari, 2026)
Regional Regulations (Peraturan Daerah or Perda) are important legal instruments in the implementation of regional autonomy in Indonesia. However, in practice, some regional regulations are still found to conflict with higher laws and regulations, inadequately reflect public interests, and fail to fully incorporate the values of justice and public welfare. This condition highlights the importance of harmonizing regional regulations with the principles of Siyasah Dusturiyah, an Islamic constitutional concept that emphasizes justice (al-'adalah), deliberation (syura), public welfare (maslahah), equality (al-musawah), and trustworthiness (amanah). This study aims to analyze the process of regional regulation formation in Indonesia and examine its harmonization with the principles of Siyasah Dusturiyah. The research employs a normative legal research method using statutory and conceptual approaches. Legal materials were obtained from legislation, books, and relevant scholarly journal articles and were analyzed using a descriptive qualitative method. The findings indicate that the principles of Siyasah Dusturiyah are highly relevant to the formation of regional regulations in Indonesia. Such harmonization can be achieved through the application of justice, public welfare, deliberation, equality, and trustworthiness in every stage of the legislative process. The main challenges include regulatory overlap, inadequate legal harmonization, and limited public participation. Therefore, strengthening academic manuscripts, improving regional legislative oversight, and implementing the principles of Siyasah Dusturiyah in legal drafting are necessary to produce high-quality, just, and welfare-oriented regional regulations.